Identification of Cucumber mosaic resistance 2 (cmr2) That Confers Resistance to a New Cucumber mosaic virus Isolate P1 (CMV-P1) in Pepper (Capsicum spp.) - Choi, Seula; Lee, Joung-Ho; Kang, Won-Hee; Kim, Joonyup; Huy, Hoang N.; Park, Sung-Woo; Son, Eun-Ho; Kwon, Jin-Kyung; Kang, Byoung-Cheorl (Frontiers in Plant Science, 2018)
Cucumber mosaic virus (CMV) is one of the most devastating phytopathogens of Capsicum. The single dominant resistance gene, Cucumber mosaic resistant 1 (Cmr1), that confers resistance to the CMV isolate P0 has been overcome by a new isolate (CMV-P1) after being deployed in pepper (Capsicum annuum) breeding for over 20 years. A recently identified Indian C. annuum cultivar, “Lam32,” displays resistance to CMV-P1. In this study, we show that the resistance in “Lam32” is controlled by a single recessive gene, CMV resistance gene 2 (cmr2). We found that cmr2 conferred resistance to CMV strains including CMV-Korean, CMV-Fny, and CMV-P1, indicating that cmr2 provides a broad-spectrum type of resistance. We utilized two molecular mapping approaches to determine the chromosomal location of cmr2. Bulked segregant analysis (BSA) using amplified fragment-length polymorphism (AFLP) (BSA-AFLP) revealed one marker, cmvAFLP, located 16 cM from cmr2. BSA using the Affymetrix pepper array (BSA-Affy) identified a single-nucleotide polymorphism (SNP) marker (Affy4) located 2.3 cM from cmr2 on chromosome 8. We further screened a pepper germplasm collection of 4,197 accessions for additional CMV-P1 resistance sources and found that some accessions contained equivalent levels of resistance to that of “Lam32.” Inheritance and allelism tests demonstrated that all the resistance sources examined contained cmr2. Our result thus provide genetic and molecular evidence that cmr2 is a single recessive gene that confers to pepper an unprecedented resistance to the dangerous new isolate CMV-P1 that had overcome Cmr1.